Cartographies of the Crisis in Esta Herida Llena de Peces by Lorena Salazar; [Cartografías de la Crisis en Una Herida Llena de Peces de Lorena Salazar*]; [Cartographies de la Crise Dans Esta Herida Llena de Peces de Lorena Salazar] - Navarrete-Barria, S (Universidad de Granada, 2023)
This paper proposes a geographical look at the imaginaries of crisis in re-cent Latin-American literature, concentrating on its spatialities. In these imaginaries we observe a clear referential intention that aims to evidence, denounce and problema-tize the crisis from the violence of the territories. Within this framework of interpretation, we postulate as a general hypothesis that this accentuation of spatial work allows us to approach the imaginaries of the crisis, no longer with a view to the future, from post-apocalyptic or dystopian representations, but as something coexistent with the reader’s time. In this way, the focus on the spatial axis makes it possible to reflect on the immediacy and coexistence of the crisis, placing the different types of violence in the territories as a valid point to articulate the Latin American and Caribbean crisis. To deepen this hypothesis, we will limit our study to the novel Esta herida llena de peces by Lorena Salazar (2021). © 2023, Universidad de Granada. All rights reserved.